A Survey of Unmixed Bipartite Graphs and Very Well-Covered Graphs (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Many authors investigated unmixed and bipartite graphs. There are many results obtained on these two types of graphs and show that a bipartite graph  G  satisfies Serre’s condition  S2, then G is Cohen-Macaulay. This paper is a survey with some new results about very well-covered graphs, an unmixed bipartite graph.